Government Strategy To Improve Public Acceptance Toward Nuclear Power Plant - Aritonang, Sovian; Parlina, Nining; Kuntjoro, Yanif Dwi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2018)
This research to discuss the Government's strategy to increase public acceptance toward nuclear power development plan. The purpose of this research is to obtain recommendation for government’s strategy. It is design as descriptive qualitative one with design research. The results showed there are two strategies, namely; strategies of socialization through counseling and through online media. Based on the research, it is recommended that the government should establish a Coordination Board which is under the command of (under command) specifically in the case of nuclear power plants in Jepara. Keywords: Nuclear Power Plant; Community acceptance; The government's strategy.